FOREST FIRE PREDICTION SYSTEM - Hendro Priyatman; Dewanto Rosian Adhy (Suara Teknik : Jurnal Ilmiah, 2010)
The tropical forest there are being one of natural resources that need toprotect and explorate wise and safely also sustainabilty concept. But at severalyears later, there are some problems causes by improperly exploitation. One ofdisaster is forest fire. This disater not only eliminate forest natural resources butalso produce other disaster like fogging and disturbing ecosystem. On the otherside, research development at intelligence system especially neurofuzzy producedesign system that able to make monitoring to real data, proceed with rule baseform human thinking and produce proediction system and supportinginformation from decision making. Regarding to two point of view describeabove, exist one idea to using development and achievment at neurofuzzyconcept to make monitoring about ecological especially forest fire condition andproceed and make prediction to anticipate it.Keywords: forest, fire, neurofuzzy.